The relationship between maternal characteristics and early childhood caries - Susi, Susi; Murniwati, Murniwati; Kasuma, Nila; Minarni, Minarni (Universitas Padjadjaran, 2020)
Introduction: World Oral Health Organization (WHO) targeted in 2010 that 90% of children under five years are caries-free. In 2011, the prevalence of Early Childhood Caries (ECC) was 6%-90% worldwide. It is still far from the WHO target. Many factors can cause caries; one of them was family characteristics. The objective of the study was to analyse the relationship between maternal characteristics (education, occupation, and the number of children) and early childhood caries. Methods: A cross-sectional study was conducted in the Integrated Post Service (Posyandu) located in the city of Bukittinggi, Indonesia. The sample was 66 parents and their children aged 2-3 years. Maternal characteristic was obtained by interview, whereas the ECC was measured using the def-t index. Data were collected and analysed by the Chi-square test. Three dentists and two dentistry students collected the calibrated data. Results: ECC prevalence was 50% (CI 95%; 38%-62%) with the def-t index of 2.23 ± 2.81 (CI 95%; 1.53-2.92) and caries significant index (CSI) was 5.73. The prevalence of caries-free was found highest in children with working mothers (66.7%) and the lowest (31.6%) in children with basic educated mothers. The highest def-t index was 3.17± 3.212, which was found in three-years-old children, and the lowest was 1.98 ± 2.915, which was found in children with advance educated mothers. Conclusion: There was no relationship between maternal education level, occupation, and the number of children with early childhood caries.